Industrial Partnership and Local Wisdom in the Rattan Furniture Industry: An Anthropological Perspective in Maintaining Cultural Heritage and Innovation - Boike Janus Anshory; Prihandoko Sanjatmiko (Jurnal Syntax Transformation, 2023)
This research aims to the partnership between the rattan furniture industry and local wisdom from an anthropological perspective has become an important part of the cultural heritage of certain communities, and illustrates the close relationship between humans and nature and traditions that continue to be preserved from generation to generation. With the development of technology and globalization, challenges arise in maintaining cultural authenticity while still innovating to meet changing market demands. The stage is to explore how a solid partnership between the rattan furniture industry and the local community can be the key to maintaining and appreciating local wisdom. Anthropology as a scientific approach will assist in understanding the important role of culture and traditional values in the production process and design of rattan furniture. This research is a relevant and meaningful forum for discussing how the rattan furniture industry can collaborate with anthropology-based local communities. By applying an anthropological perspective in an industrial context, a deeper understanding of the role of rattan furniture as part of cultural heritage and local identity will be obtained. Descriptions of creative and innovative ways to integrate traditional values and local wisdom in the rattan furniture production process will have an impact on sustainable and mutually beneficial partnerships between industry and local communities will be discussed to maintain and appreciate knowledge and skills that have been passed down from generation to generation. The role of the rattan furniture industry is expected to be able to adapt to the challenges of globalization, while still maintaining the authenticity of their products and supporting cultural sustainability in the context of implementing local values, the design and marketing of rattan furniture products in the global market will be an important focus point. By analyzing the impact of globalization and technology on the rattan furniture industry, it is hoped that it will encourage active participation and collaboration from industry players, academics and local communities in maintaining cultural wealth and creativity in the rattan furniture sector